Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I know my math is very rusty, actually, its always been that way. but I need help with this. The question below has me stumped. I've tried to show the steps I went through to get the answer. Please tel me where I made the mistake.


If x=a and x=b are two roots of a quadratic equation then (x-a)(x-b) = 0 gives the quadratic equation.

That is $(x - a)(x - b) = x^2 - (a + b)x + ab = 0$.

Here, the two roots are $x= -2 + j\sqrt5$ and $x = -2 - j\sqrt5$ so that $(x – [-2 + j\sqrt5])(x – [-2 - j\sqrt5]) = 0$

That is $x^2 - x[-2 + j\sqrt5 - 2 - j\sqrt5] + [-2 + j\sqrt5][-2 - j\sqrt5] = 0$

I understand that

$x^2 - x[-2 + j\sqrt5 - 2 - j\sqrt5] + [-2 + j\sqrt5][-2 - j\sqrt5] = 0$
$x^2 - x[-2 - 2] + [-2 + j\sqrt5][-2 - j\sqrt5] = 0$, and
$x^2 - x[-4] + [-2 + j\sqrt5][-2 - j\sqrt5] = 0$, so
$x^2 + 4x + [-2 + j\sqrt5][-2 - j\sqrt5] = 0$

if we separate out the last term for simplicity: $[-2 + j\sqrt5][-2 - j\sqrt5] = (-2)(-2) + (-2)(-j\sqrt5) + (-2)(+j\sqrt5) + (+j\sqrt5)(-j\sqrt5)$ $= 4 + (2j\sqrt5) - (2j\sqrt5) +(-j\sqrt5)^2$
$ = 4 + (2j\sqrt5) - (2j\sqrt5) +(-j^2)(-\sqrt5)^2$
$ = 4 +j^2 5$

Putting this last term back into the main equation results in:
$x^2 + 4x + (4+j^2 5) = 0$

In the book (Advanced Engineering Mathematics)* this equation works out to
$x^2 + 4x + 9 = 0$

What I don’t understand is what happened to $j^2$ How does it just magically disapear?

*If you use the Amazon "Look inside" feature you can see it on page 4.

share|improve this question
1  
The last line in the sequence of equations after "if we seperate put the last term for simplicity" should be $4-j^25$, as $(-j^2)(-\sqrt{5})^2=-j^25$. This gives us $4-5j^2=4-(-1)\cdot 5=9$, because $j=\sqrt{-1}$. –  Alex Becker Apr 3 '12 at 21:12
1  
You have to be careful with signs: $(-j)(+j) = -j^2$ is not the same as $(-j)^2$. –  Dejan Govc Apr 3 '12 at 21:17
4  
As the son of an electrical engineer, I learned to use the letter $j$ for $\sqrt{-1}$ before I learned to use $i$. Here's something that's happened to me several times with undergraduates. I'm doing some routine calculation in which $i^2$ appears, and a student show claims to be well aware of the fact that $i=\sqrt{-1}$ does not know what $i^2$ is. I ask if they know what $\sqrt{83}\cdot\sqrt{83}$ is, and they say: not without a calculator. I ask: Do you know what square roots are? They say "yes". Then I say $\sqrt{83}\cdot\sqrt{83}$ is $83$. Then I'm asked how I got that. –  Michael Hardy Apr 3 '12 at 21:19
3  
@MichaelHardy $*$ shudder $*$ –  anon Apr 3 '12 at 21:27
5  
@anon You think that's bad? As the son of an Econ professor, I hear way worse. The one that takes the cake is a student asking for a calculator on an exam to simplify $\frac{120}{1}$. –  Alex Becker Apr 3 '12 at 21:36

1 Answer 1

up vote 5 down vote accepted

Here are your steps with mistakes highlighted in red:

$[-2 + j\sqrt5][-2 - j\sqrt5] = (-2)(-2) + (-2)(-j\sqrt5) + (-2)(+j\sqrt5) + (+j\sqrt5)(-j\sqrt5)$ $= 4 + (2j\sqrt5) - (2j\sqrt5) + \color{red}{(-j\sqrt5)^2}$
$ = 4 + (2j\sqrt5) - (2j\sqrt5) + \color{red}{(-j^2)(-\sqrt5)^2}$
$ = 4 + \color{red}{j^2 5}$

Here is fixed, with highlighting in red:

$[-2 + j\sqrt5][-2 - j\sqrt5] = (-2)(-2) + (-2)(-j\sqrt5) + (-2)(+j\sqrt5) + \color{blue}{(+j\sqrt5)(-j\sqrt5)}$ $= 4 + (2j\sqrt5) - (2j\sqrt5) +\color{red}{(-1)\times j^2\times (\sqrt5)^2}$
$ = 4 + (2j\sqrt5) - (2j\sqrt5) +\color{red}{(-1)\times (-1)\times 5}$
$ = 4 +\color{red}{5} = 9$

Note that

$$\color{blue}{(+j\sqrt5)(-j\sqrt5)} = \color{red}{(-1)\times j^2\times (\sqrt5)^2}$$

and

$$j^2 = -1$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.